Distributed ledger technology for securities clearing and settlement: Benefits, risks, and regulatory implications - Randy Priem (Financial Innovation, 2020)
This article outlines the benefits and risks of the distributed ledger technology (DLT) for the clearing and settlement of exchange-traded and OTC securities, followed by a description of the technology's potential role for central counterparties and central securities depositories. Although the industry and scholars are attempting to solve the technological and operational issues that DLT systems still face, outstanding legal risks are such that the financial industry is asking for more regulatory guidance and intervention. This article wants to contribute to the public policy debate by presenting potential regulatory barriers that may have to be removed for DLT to be fully adopted. In addition, it identifies areas requiring an update of the legal framework in order to address certain prudential and conduct risks that this technology could introduce.
Keywords: E44; G15; G18; G21; K22; 650; Distributed ledger technology; Blockchain; Clearing; Settlement; and financial regulation